Art Mediation: Philosophy, Aesthetics, and Practice - Venkova, Alina V. (Actual Problems of Theory and History of Art, 2021)
The article shows the theoretical, aesthetic, and educational foundations of the artistic mediation. Based on the philosophical (M. Heidegger), sociological (B. Latour), and aesthetic (N. Bourriaud, C. Bishop) approaches to understanding the phenomenon of mediation, it reveals the main principles of the instrumental (D. Dewey), critical (P. Freire, P. McLaren, A. Giroux, M. Barber), situational (P. Freire, D. Haraway), and collaborative pedagogy (K. Bruffee, N. Simon) united by the concept of “educational practices of participation”. The aim was to show the existing forms of art mediation available to artists, spectators, social educators, and organizers of public programs, both inside and outside of museums and galleries.These forms include verbal, body oriented, instrumental, environmental, participatory, performative, inclusive, and online mediation. The potentiality of various forms of mediation have been shown on the example of significant art projects where mediation practices were created, developed, and demonstrated by the artists themselves (Joseph Beuys, Artur Żmijewski, the Microsillons Group, Rirkrit Tiravanija, Shia LaBeouf, Nastja Säde Rönkkö & Luke Turner, Tino Sehgal, the School of Engaged Art — Chto Delat Group, North 7 Group).
Keywords: art mediation; participation; relational aesthetics; participatory pedagogy; instrumental pedagogy; critical pedagogy; situational pedagogy; participatory practices